Irrigation scheduling technologies reduce water use and maintain turfgrass quality. (7th May 2020) - Serena, Matteo; Velasco‐Cruz, Ciro; Friell, Joshua; Schiavon, Marco; Sevostianova, Elena; Beck, Leslie; Sallenave, Rossana; Leinauer, Bernd
Abstract: Smart irrigation controllers have demonstrated potential for turfgrass water conservation in humid and temperate environments but have not been comprehensively tested in arid environments. The objective of this study was to determine the accuracy of a wireless capacitance sensor over a wide soil moisture range and to ascertain if smart irrigation controllers resulted in water savings without reducing quality of tall fescue [ Schedonorus arundinaceus (Schreb.) Dumort.] and bermudagrass ( Cynodon dactylon L.). A two‐yr study was conducted to compare turfgrass quality, root morphology, and water use of plots irrigated with a constant run time to plots for which irrigation was scheduled using soil moisture sensors (SMS), evapotranspiration (ET) [Climate Logic (CL)] controllers, or 80% of historic ET (ET80) for tall fescue and 60% (ET60) for bermudagrass. Sensors accurately tracked soil moisture up to salinity levels of 4 dS m −1 . Turf performance and root morphology were not affected by irrigation treatments for either grass. Compared to tall fescue plots irrigated with constant run time, plots irrigated using ET80 and CL required 38% less water, and SMS plots used 44% less than tall fescue. Scheduling bermudagrass irrigation by ET60, CL, and SMS resulted in a 29, 42, and 39% reduction in water applied compared to constant run time. The majority of water savings was in spring and fall. Water requirement for bermudagrass during the summer did not differ between the scheduling treatments. Our study confirms that smart irrigation controllers can be used as an effective measure to conserve water in an arid environment.